2001
DOI: 10.1016/s0378-1097(01)00114-8
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of aspirin-sensitive oxylipins in vulvovaginal candidiasis

Abstract: 3(R)-Hydroxyoxylipins are produced via an aspirin-sensitive pathway in Candida albicans, an abundant pathogen in vulvovaginal candidiasis. In the present study, we have investigated the effect of aspirin on vaginal isolates of C. albicans from patients with recurrent candidiasis. Aspirin alone and with clotrimazole, a commonly used drug, strongly suppressed growth of C. albicans. 3(R)-Hydroxyoxylipins, which were selectively located in hyphae and other filamentous structures, but not in free blastospores, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…It is suggested that 3-OH oxylipins are produced through incomplete b-oxidation in the mitochondria which is then released and deposited on amongst others ascospore surfaces . It is also reported that ASA inhibits b-oxidation in mitochondria and coiling around each other to keep these ascospores in small groups, are shown in (b) therefore 3-OH oxylipin synthesis (Deva et al 2001;Glasgow et al 1999). According to Glasgow and co-workers (1999), salicylate, the primary metabolite of aspirin inhibits b-oxidation of medium and long-chain fatty acids in rodent liver mitochondria but not peroxisomes.…”
Section: Eremothecium Gossypiimentioning
confidence: 92%
See 1 more Smart Citation
“…It is suggested that 3-OH oxylipins are produced through incomplete b-oxidation in the mitochondria which is then released and deposited on amongst others ascospore surfaces . It is also reported that ASA inhibits b-oxidation in mitochondria and coiling around each other to keep these ascospores in small groups, are shown in (b) therefore 3-OH oxylipin synthesis (Deva et al 2001;Glasgow et al 1999). According to Glasgow and co-workers (1999), salicylate, the primary metabolite of aspirin inhibits b-oxidation of medium and long-chain fatty acids in rodent liver mitochondria but not peroxisomes.…”
Section: Eremothecium Gossypiimentioning
confidence: 92%
“…Consequently, the use of non-steroidal anti inflammatory drugs (NSAIDs) such as aspirin as antifungals that act on these target sites has been suggested (Kock and Coetzee 1990). These oxylipins were later found in various yeasts (Ciccoli et al 2005;Deva et al 2000Deva et al , 2001Deva et al , 2003Kock et al 2003;Noverr et al 2003;Van Heerden et al 2005) while subsequent studies further exposed these oxylipins as new target sites for developing novel antifungals Douglas 2004, 2005;Erb-Downward and Huffnagle 2006;Noverr et al 2003). Literature also suggests that 3-OH oxylipins are associated with the surfaces of ascospores where they probably assist in ascospore release from enclosed asci via for example turgor pressure (Fisher et al 2004;Kock et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans infections are associated with the release of the bioactive molecule, arachidonic acid (AA), from the infected host cell membrane [4,5]. The released AA can be used as a carbon source by C. albicans and as a precursor for the synthesis of yeast eicosanoids such as prostaglandin E 2 (PGE 2 ) by C. albicans [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The released AA can be used as a carbon source by C. albicans and as a precursor for the synthesis of yeast eicosanoids such as prostaglandin E 2 (PGE 2 ) by C. albicans [6,7]. Eicosanoids are involved in C. albicans infection, aVecting the host's immune responses, enhancing vascular permeability and facilitating the invasion of the host tissue/cells, as well as enhancing germ tube formation [5,8,9]. The production of eicosanoids by C. dubliniensis has not been studied, although its close relationship to C. albicans [1] might point to similar ability to produce eicosanoids.…”
Section: Introductionmentioning
confidence: 99%
“…These authors and other studies had reported the involvement of multicopper oxidase enzymes and cytochrome P450 enzymes (CYP) in the PGE2 production by C. albicans and C. dubliniensis biofilms (Erb-Downward and Noverr 2007;Erb-Downward et al 2008;Ells et al 2011). Moreover, antifungal effects attributed to aspirin have been associated with inhibiting the formation of 3(R)-hydroxyoxylipins (Deva et al 2001) and of an extracellular fungal lipase (Trofa et al 2009). Sodium salicylate also has antiinflammatory activity; it is less effective than aspirin and reversibly inhibits both COX-1 and COX-2 (Mitchell et al 1994;Wu 2000;Amann and Peskar 2002).…”
Section: Resultsmentioning
confidence: 94%